Analisis Laporan Rasio Profitabilitas Keuangan, PT Mayora Indah Tbk 2016-2020 - Nirwana Sari; Kristin Natalia; Wilda Dwina; Laily Ramadhani (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the financial performance of PT Mayora Indan Tbk over the period 2016-2020 using financial ratios- including gross profit margin, operating profit margin,net profit margin, retrun on investment (ROI), and retrun on equity (ROE). The company showed strong profitability in 2016, but experienced sharp declines in various margins in 2017 and 2018, followed by moderate recovery in 2019, then a slight setback in 2020 due to reduced sales.despite decreasing trends,key profitability indicatros remained within healty ranges. PT Mayora Indan Tbk maintained liquidity and generated net income consistently, although the ratio of net income growth to equity remained modest.the findings suggest that while the firm’s financial condition remained sound,it should enhance asset and improve its profitability in the future.